Phytochemical screening and in vitro biological activity of Amaranthus viridis growing in Northern Cyprus - Ümit Haydar Erol; Aysun Mercimek Takcı; Fikret Büyükkaya Kayış; Melis Sümengen Özdenefe (International Journal of Secondary Metabolite)
In this study, phenolic and non-phenolic metabolites in different parts of A. viridis (from the Turkish Republic of Northern Cyprus) were characterized with reversed-phase high-performance liquid chromatography (RP-HPLC) with diode array detector and high-performance liquid chromatography (HPLC), respectively. In total, approximately twenty-five phenolic compounds including quercetin, chrysin, t-Ferulic acid, and sinapic acid as the most abundant secondary metabolites were identified. On the other hand, four organic acids as non-phenolic compounds quantitatively predominant were identified for the first time in A. viridis extracts. The seed and flower extract showed strong ferric-reducing capacity, radical scavenging activity for DPPH˙, phosphomolybdenum assay, metal chelating, and α-amylase inhibition activity by in vitro assays. Our results suggest that A. viridis widely used in the human diet in Cyprus is a source of numerous metabolites showing antioxidant and antibacterial potential.